Infographics : the power of visual storytelling - Lankow, Jason; Ritchie, Josh.; Crooks, Ross. (Hoboken, N.J. : John Wiley & Sons, Inc., 2012)
Explains how infographics use visual communication to attract, inform, and entertain their audience.
Importance and efficacy: why our brains love infographics : Varied perspectives on information design ; A brief history ; Objectives of visualization ; Appeal ; Comprehension ; Retention -- Infographic formats: choosing the right vehicle for your message : Static infographics ; Motion graphics ; Interactive infographics -- The visual storytelling spectrum: an objective approach : Understanding the visual storytelling spectrum -- Editorial infographics : What are editorial infographics? ; Origins of editorial infographics ; Editorial infographic production -- Content distribution: sharing your story : Posting on your site ; Distributing your content ; Patience pays dividends -- Brand-centric infographics : "About us" pages ; Product instructions ; Visual press releases ; Presentation design ; Annual reports -- Data visualization interfaces : A case for visualization in user interfaces ; Dashboards ; Visual data hubs -- What makes a good infographic? : Utility ; Soundness ; Beauty -- Information design best practices : Illustration ; Data ; Visualization -- The future of infographics : Democratized access to creation tools ; Socially generative visualizations ; Problem solving ; Becoming a visual company.
Includes index.
Includes bibliographical references and index.
Keywords: Visual communication; Communication -- Graphic methods; Information visualization; Business presentations; Presentation graphics software; Business presentations; Communication -- Graphic methods; Information visualization; Presentation graphics software; Visual communication